Pegaruh Budaya Kampus Terhadap Kepatuhan Mahasiwa terhadap Etika Akademik - Suhaila Irfi; Rafi Alumutaqin; Mhd Zaky; Zaki Albukhari Persada Simatupang; Norma Hanum Harahap (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Academic ethics violations such as plagiarism, cheating in examinations, and academic responsibility are serious problems in the field of education. This study aims to examine how campus culture affects students' ethical behavior in the academic context. The approach used is qualitative, with data collection methods including document study, participatory observation, and in-depth interviews. The findings reveal that a conducive campus culture—characterized by exemplary behavior of lecturers, enforcement of ethical codes, and consistent internalization of moral values—plays a significant role in enhancing students’ adherence to academic ethics. Conversely, an academic environment that is permissive toward ethical violations negatively impacts students’ character. This study concludes that the establishment of a strong academic culture is a key factor in fostering academic integrity among university students.